Neighborhood crime is differentially associated with cardiovascular risk factors as a function of race and sex - Mollie R. Sprung; Lauren M.D. Faulkner; Michele K. Evans; Alan B. Zonderman; Shari R. Waldstein (SAGE Publishing, 2019)
Background: Neighborhood crime may be an important factor contributing to cardiovascular health disparities, and these relations may vary by race and sex. The present investigation evaluated (a) potential differential associations between neighborhood crime and cardiovascular disease (CVD) risk factors within subgroups of African American (AA) and White men and women, and (b) potential mediation by negative affect. Design and Methods: Participants were 1,718 AAs and Whites (58% AA; 54% female; 59% above poverty; ages 30-64 years) living Baltimore, Maryland who completed the first wave of the Healthy Aging in Neighborhoods of Diversity across the Life Span study from 2004-2009. CVD risk factors included body mass index, total serum cholesterol, glucose, and systolic and diastolic blood pressure. A negative affect composite was comprised of self-reported depression, anxiety, anger, vigilance, and perceived stress. Hierarchical multiple regression analyses were used to examine associations between per capita overall and violent crime rates, negative affect, and CVD risk factors. Results: There were significant associations of greater overall crime rate with higher fasting glucose (b=.192, P<0.05), and greater violent crime rate with higher systolic (b=86.50, P<0.05) and diastolic (b=60.12, P<0.05) blood pressure in AA women, but not men. These associations were not explained by negative affect. In Whites, there were no significant associations of overall or violent crime rates with cardiovascular risk factors. Conclusions: AA women may be particularly vulnerable to the negative impact of crime on cardiovascular risk. Preventative efforts aimed toward this group may help to deter the detrimental effects that living in a high crime area may have on one's cardiovascular health.